RESULTS OF RADISH BREEDING ON THE MORPHOLOGICAL DIVERSITY OF ROOT CROPS - A. M. Tsiunel (Овощи России, 2017)
One of directions of radish breeding is creation of varieties with an unusual combination of color and form of a root crop. The article presents the results of the breeding work with radish and introduces description of 7 new radish varieties.